Predictors of Blood Pressure Target Achievement in Tolaki and Muna Ethnic Groups Undergoing Candesartan Cilexetil Monotherapy: A Quasi-Experimental Study - Zullies Ikawati; Agung Endro Nugroho; Ismail Setyapranoto; Mesi Leorita (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2025)
Therapy adherence, sociodemographic factors, and lifestyle are factors that influence the achievement of blood pressure targets in hypertensive patients. This study aims to compare and examine the impact of therapy adherence, Sociodemographic, ethnicity, and lifestyle on the achievement of blood pressure targets in hypertensive patients of Muna and Tolaki ethnicities undergoing candesartan cilexetil monotherapy. This study employed a quasi-experimental design with a comparison group approach. A total of 147 patients were selected via consecutive sampling and categorized by ethnicity: Tolaki (n = 75) and Muna (n = 72). Both groups received a standardized dose of Candesartan Cilexetil (8 mg). The primary outcome was the change in blood pressure from baseline (pretest) to day 30 (posttest). Adherence, monitored via pill count, along with sociodemographic and lifestyle factors, was analyzed as a covariate to ensure a robust evaluation of the treatment's clinical impact across both ethnic groups. There was no significant difference in therapy adherence between participants of both ethnicities (p = 0.78). However, Tolaki participants experienced a greater reduction in 30-day systolic and diastolic blood pressure compared to Muna participants (p = 0.00). Furthermore, a greater percentage of Tolaki participants achieved blood pressure therapy targets (76%) compared to Muna participants (15.28%) (p < 0.001). Multivariate logistic regression analysis revealed that two variables that most significantly influence the attainment of blood pressure objectives are ethnicity (Tolaki ethnicity) (OR 21.44, 95% CI 6.69–53.40, and p=0.00) and a high level of therapy adherence (OR 10.89, 95% CI 2.96–40.07, and p=0.00). Ethnicity and therapy adherence are two important factors that need to be considered in efforts to achieve blood pressure therapy targets in the Tolaki and Muna tribes undergoing candesartan cilexetil monotherapy.